2011
DOI: 10.1007/s11481-011-9303-6
|View full text |Cite
|
Sign up to set email alerts
|

Morphine, but Not Trauma, Sensitizes to Systemic Acinetobacter baumannii Infection

Abstract: Acinetobacter baumannii is an important nosocomial pathogen in civilian intensive care units. Recently the incidence has increased in wounded military personnel. Morphine is documented in numerous animal studies to be immunosuppressive and to sensitize to infection. The hypotheses were tested that morphine, administered for analgesia in the battlefield, predisposes to Acinetobacter infection, and that the opioid may have an additive or synergistic effect with trauma. To test these hypotheses, an intraperitonea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 63 publications
0
30
0
1
Order By: Relevance
“…Breslow et al found that morphine treatment resulted in a marked enhancement of death in mice from intraperitoneal infection by clinical isolates of A. baumannii (130). Naltrexone, an opiate antagonist, reversed the effect, demonstrating the specificity of the opiate effect.…”
Section: More-recent In Vivo Virulence Assessmentsmentioning
confidence: 99%
“…Breslow et al found that morphine treatment resulted in a marked enhancement of death in mice from intraperitoneal infection by clinical isolates of A. baumannii (130). Naltrexone, an opiate antagonist, reversed the effect, demonstrating the specificity of the opiate effect.…”
Section: More-recent In Vivo Virulence Assessmentsmentioning
confidence: 99%
“…These efforts include both murine and rat pulmonary models of infection. The murine models have relied upon mucin (12), cyclophosphamide (13), or morphine (14) to establish the infection, and yet another model used diabetic mice (15). Besides the rat pulmonary model developed by Russo et al (16), that group also developed an abscess model of infection in the same study (16).…”
mentioning
confidence: 99%
“…In these environments, adequate personnel for monitoring may not be available, leaving respiratory depression and sedative effects of opioids unrecognised. Opioids are also known to cause immunosuppression and may lead to susceptibility to Acinetobacter infection [41], a major cause of wound infection in this population. For all these reasons, modern conflict analgesia is steering away from opioids and towards multimodal analgesia and novel ways to treat pain.…”
Section: Pain From Warmentioning
confidence: 99%